Laburnicola haloxyloni sp. nov., a new endophytic species isolated from roots of Haloxylon persicum in Iran - Mehrabi, Mehdi (Phytotaxa, 2026)
In this study, a new endophytic fungal species, Laburnicola haloxyloni, is introduced from the roots of Haloxylon persicum collected in North Khorasan Province, Iran, based on morphological characteristics and phylogenetic evidence. The species is known only from its asexual morph and is characterized by immersed, brown, globose to ellipsoidal or pyriform conidiomata, enteroblastic, ampulliform to cylindrical conidiogenous cells and oblong to cylindrical, hyaline, aseptate conidia. Phylogenetic analyses of combined ITS, LSU, and SSU sequence data support Laburnicola haloxyloni as a distinct species within Laburnicola. A detailed description, illustrations, and a phylogenetic tree are provided.